1988
DOI: 10.1007/bf00172114
|View full text |Cite
|
Sign up to set email alerts
|

Properties of cardiac alpha- and beta-adrenoceptors in spontaneously hypertensive rats

Abstract: The effects of isoprenaline, Ca2+ and phenylephrine (in the presence of propranolol) on force of contraction were studied in isolated electrically driven papillary muscles of spontaneously hypertensive rats (SHR) and age-matched (14-18 weeks) Wistar Kyoto control rats (WK). Cardiac alpha- and beta-adrenoceptors were characterized by radioligand binding studies. The positive inotropic effect of isoprenaline in SHR was less effective than in control rats. The EC50 values did not differ in both groups. In SHR, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…The al-adrenoceptor agonist, phenylephrine, produced significantly smaller maximal responses in both atrial and ventricular tissues than calcium chloride or the a-and PI-adrenoceptor agonist, noradrenaline. Similar results have been reported in left ventricular papillary muscles (Bohm et al 1988b) and atrial tissues (Wagner & Brodde 1978). Phenylephrine produced small chronotropic responses in rat right atria ( Fig.…”
Section: Discussionsupporting
confidence: 86%
“…The al-adrenoceptor agonist, phenylephrine, produced significantly smaller maximal responses in both atrial and ventricular tissues than calcium chloride or the a-and PI-adrenoceptor agonist, noradrenaline. Similar results have been reported in left ventricular papillary muscles (Bohm et al 1988b) and atrial tissues (Wagner & Brodde 1978). Phenylephrine produced small chronotropic responses in rat right atria ( Fig.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is in agreement with several other reports (22)(23)(24). On the other hand, it has been reported that the number of cardiac fl-adrenoceptors in SHR is smaller than that in WKY (25)(26)(27). The reason for this discrepancy remains unknown.…”
Section: Discussionsupporting
confidence: 93%
“…SHRs have a selectively reduced responsiveness to norepinephrine and other adrenergic stimulation. 61 Furthermore, the development of heart failure, rather than hypertension or hypertrophy, may be the important step in the decreased responsiveness or increased toxicity to norepinephrine. 62 Intrinsic impairments of the nitric oxide system 32,63 together with elevated vascular oxidative stress 64,65 in SHRs would both contribute to the impairment of vascular relaxation responses seen in this study.…”
Section: Discussionmentioning
confidence: 99%